ANALISIS PENGUMUMAN PEMBAGIAN DIVIDEN TERHADAP HARGA SAHAM DAN ABNORMAL RETURN PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - R. Nalole, Utami Parfitasari; Nurdin, Djayani; Kasim, Muhammad Yunus (Katalogis, 2018)
The study intends to determine and analyze the average difference of stock price and abnormal return before and after dividend announcement in manufacture industry on Indonesia stock exchange in the period of 2012-2016. Secondary data is used with event study method, in this case is the announcement of dividend share. Population consist of 128 companies listed on Indonesia stock exchange in 2012-2016. Sampling technique used is purposive sampling to select 10 companies as sample. Data analysis technique is paired sample t-test with 10 observation days; 5 days before and 5 days after the dividend announcement date. The test results indicate that there is no significant difference between the average stock price and abnormal return before and after dividend is announced.